Feeding Strategies of Great Blue Herons (Ardea herodias fannini) in False Bay, San Juan Island - Rillera, Rachel; Sebek, Maia; Vitruk, Olga (Friday Harbor Laboratories, 2014)
Abundance and foraging habits in Great Blue Herons (Ardea herodias fannini) are correlated with habitat type, tide phase and height, and group size in False Bay in the San Juan Islands, Washington. We completed field surveys during 9-18 August 2014 at False Bay to examine general heron abundance and strike rate success for different habitats, tide phases and heights, and heron group sizes. Total abundance was assessed along with location in the bay, habitat type, water depth, and tide phase and height for each individual. We assessed strike rate success for individuals, noting the five criteria above as well. The results from foraging observations indicated that herons at False Bay had greater strike rate successes behind the tideline and in deeper water, and during higher and flood tides. Such success patterns could relate to prey abundance, size, and profitability. We also found the success rate of individual herons to be greater when foraging alone or in groups of six or more. These success patterns could be due to competition factors, as well as herons using one another as indicators of food availability. Additionally, we found heron abundance and success rate appear inversely related in some cases, which may be related to prey depletion. Congruent with findings from previous studies, this study indicates a correlation between heron foraging success and the aforementioned habitat, tide, water depth, and group features.
Keywords: Great Blue Heron, Ardea herodias, False Bay, San Juan Island, strike rate, foraging, abundance, tide height, tide phase